Digitalization Challenges for SMEs: A Systematic Literature Review Perspective and Future Research - Ietje Nazaruddin; Evy Rahman Utami; Evi Rahmawati (Universitas Muhammadiyah Yogyakarta, 2024)
SMEs are a fundamental component of the economic structure in many countries. In the contemporary era of digitalization, SMEs are undertaking various initiatives to align with the evolving business landscape. This study aims to explore and synthesize research results on the role of digitalization in developing small and medium enterprises (SMEs). The literature review used the Scopus database. The data obtained were 127 documents from 2010 to 2023. SME digitization research has been conducted in 42 countries using 92 theories from 94 journals. The results showed three research clusters: business model innovation, Enterprise Resource Planning (ERP), and Information Technology (IT) capabilities. Digital platforms and information management assist SMEs in adjusting, creating new ideas, and staying competitive in difficult business circumstances. Digital platforms assist SMEs by extending market reach, automating operations, improving marketing and promotional efforts, analyzing consumer data to make better decisions, and strengthening team communication and customer care. Future research investigates effective strategies and educational programs aimed at helping SMEs acquire digital skills, adopt digital technology, and implement advanced blockchain-based contract systems. Future research also investigates the ethical implications of SME digitalization, encompassing issues related to data privacy, digital security, and the appropriate use of emerging technologies.